Toward Defining the Foundation of the MD Degree: Core Entrustable Professional Activities for Entering Residency. (October 2016) - Englander, Robert; Flynn, Timothy; Call, Stephanie; Carraccio, Carol; Cleary, Lynn; Fulton, Tracy B.; Garrity, Maureen J.; Lieberman, Steven A.; Lindeman, Brenessa; Lypson, Monica L.; Minter, Rebecca M.; Rosenfield, Jay; et al.
Abstract : Currently, no standard defines the clinical skills that medical students must demonstrate upon graduation. The Liaison Committee on Medical Education bases its standards on required subject matter and student experiences rather than on observable educational outcomes. The absence of such established outcomes for MD graduates contributes to the gap between program directors' expectations and new residents' performance. In response, in 2013, the Association of American Medical Colleges convened a panel of experts from undergraduate and graduate medical education to define the professional activities that every resident should be able to do without direct supervision on day one of residency, regardless of specialty. Using a conceptual framework of entrustable professional activities (EPAs), this Drafting Panel reviewed the literature and sought input from the health professions education community. The result of this process was the publication of 13 core EPAs for entering residency in 2014. Each EPA includes a description, a list of key functions, links to critical competencies and milestones, and narrative descriptions of expected behaviors and clinical vignettes for both novice learners and learners ready for entrustment. The medical education community has already begun to develop the curricula, assessment tools, faculty development resources, and pathways to entrustment for each of the 13 EPAs. Adoption of these core EPAs could significantly narrow the gap between program directors' expectations and new residents' performance, enhancing patient safety and increasing residents', educators', and patients' confidence in the care these learners provide in the first months of their residency training.